Chronic Pain: Among Tertiary Care Psychiatric Out-Patients in Singapore—Prevalence and Associations with Psychiatric Disorders - Pratika Satghare; Edimansyah Bin Abdin; Aditi Hombali; Wen Lin Teh; Ellaisha Samari; Boon Yiang Chua; Swapna Verma; Yee Ming Mok; Siow Ann Chong; Mythily Subramaniam (Pain Research and Management)
Objective. The study aimed to determine the prevalence and severity of chronic pain and its associations amongst psychiatric out-patients in a tertiary care hospital in Singapore. Methodology. The cross-sectional study was conducted among 290 psychiatric out-patients aged 21–65 years. Sociodemographic and clinical information, as well as data from Brief Pain Inventory-Short Form (BPI-sf), Beck’s Depression Inventory II (BDI-II), and Beck’s Anxiety Inventory (BAI) were collected. Cut points (C.P.s) dividing the sample into mild, moderate, and severe groups were created for the ratings of average pain. Eight possible cut-off values for the C.P.s between 3 and 7, representing 8 different categorical variables, were created and their relationships were examined with BPI’s set of seven interference items using multivariate analysis of variance. Sociodemographic and clinical correlates of chronic pain were determined using multinomial logistic regression analysis. Analysis of covariance was used to determine the association of BPI with continuous scores of BAI and BDI. Results. Based on the C.P. pain severity classification, 38.5% of the sample had mild pain, 22.9% had moderate pain, and 11.8% had severe pain. Patients with severe pain were more likely to be associated with older age (p≤0.006) (versus young age), less likely to be married (p≤0.025) (versus single), and more likely to have high risk for obesity (p≤0.030) (versus low risk for obesity). Participants with mild pain were seen to be significantly associated with older age (p≤0.021), whereas moderate pain (p≤0.002) and severe pain (p≤0.001) (versus no pain) were seen to be significantly associated with higher BAI scores. Conclusion. The current study observed high prevalence of pain among patients with psychiatric illness that was determined by optimal C.P.s for mild, moderate, and severe pain. Patients diagnosed with anxiety disorders and those with higher BMI were seen to be associated with pain of moderate to severe intensity. Improving the knowledge of correlates and co-morbidities of physical pain would aid in early identification, use of prophylactic strategies, and the intervention techniques to formulate basic guidelines for pain management among psychiatric population.